Le bassin minier du Nord-Pas-de-Calais. Un paysage stratifié entre projets, amnésies et créations - Fabrice Raffin; Antoine Luginbühl; Olivier Pollet (Projets de Paysage)
Based on research conducted during three years as part of the Ittecop programme (French Ministry of Ecology and French Agency for the Environment and Energy - ADEME) this paper presents a study of the landscapes of the Hénin-Carvin grouping of municipalities (in French, Communauté d’agglomération d’Hénin-Carvin - CAHC) located in the Nord-Pas-de-Calais mining area. After presenting the methodological issues involved in an analysis of the landscape dimension in regional planning projects, the article describes the landscape dynamics of projects in this part of the mining region which combine the mining heritage, environmental issues and the recent development of economic activity in the freight transport sector. At the heart of the debate is the notion that the continuous process of the production of landscapes has less to do with the implementation of a project than with the successive inter-meshing of regional development projects supported by different interacting stakeholders. These stakeholders may not always be politicians but they are, however, mainly focused on economic development issues. In this particular case, the stakeholders consider landscape issues relating to different historical levels and providing links on different scales to be of secondary importance.